مولانا گوہر رحمٰن ؒ کا منہج تفسیر:ماخذ وطریقہ کار، تحقیقی مطالعہ: Maulana Gohar Rahman's Methodology of Tafsir: Sources and Approach, A Research Study - Hidayat Ullah,; Dr. Muhammad Ismail, (Al Manhal Research Journal, 2024)
The Qur’an is a constitution and manifesto for humanity, containing solutions to all issues. This Book enlightens humanity with the light of monotheism, freeing them from the darkness of ignorance, disbelief, polytheism, atheism, and innovations. Without it, the Ummah is merely a soulless body, devoid of movement and warmth. Scholars of the Ummah have dedicated their lives to the interpretation and explanation of this Book, writing commentaries in various methodologies and styles. Among these scholars, Sheikh-ul-Qur’an Maulana Gohar Rahman (1936-2003) played a prominent role in the exegesis (Tafsir) of the Qur’an. Maulana Gohar Rahman held a unique position in the academic world. He was simultaneously a commentator on the Quran, an interpreter of Hadith, and an expert in jurisprudential sciences, excelling in all three fields. He provided invaluable services through his speeches and writings in the fields of Fatwa and contemporary issues, making it easier for courts to make decisions on religious matters. Alongside his other commitments, Maulana dedicated a significant part of his life to the service of the Quran, with his work on Uloom-ul-Qur’an being a remarkable contribution. However, his most notable service was conducting continuous tafsir sessions of the Holy Quran for 36 years. These sessions, lasting 45 days each, were held every year during the months of Ramadan and Sha'ban. He began these sessions in 1961 in Rustam Khel, District Mardan. For 10 years, he performed this duty at Jamia Masjid Mansoorah, Lahore. Just as every Qur’an commentator has a unique methodology in tafsir, Maulana Gohar Rahman also had his own distinctive approach. In the study, a few aspects of his unique methodology in his oral tafsir are presented.